Digital Technologies in Mathematics Education Advantages - Saparov Orinbasar Bakhievish (Genius Journals, 2023)
The following article provides information on the benefits of digital technologies in mathematics education. It talks about the benefits of ICT. Opinions were put forward that digital technologies make it easier for students to study mathematics, that calculations, examples and solutions performed in mathematics can be quickly, completely and legally concluded with the help of a computer.
Keywords: Skills; Mathematical; Engaging